Oroantral communication closure with Bichat adipose body: etiology, clinical and radiographics features - Matos, Jefferson David Melo de; Rodrigues, Andre Guimarães; Pinto, Alessandra Dossi; Pereira, Marília Lasmar Gomes; Souto, Lucas Augusto Pereira; Nakano, Leonardo Jiro Nomura; Lopes, Guilherme da Rocha Scalzer; Bottino, Marco Antonio; Ramos, Nathália de Carvalho; Rodrigues, Danillo Costa; Andrade, Valdir Cabral (ARCHIVES OF HEALTH INVESTIGATION, 2020)
Objective: This study aims to clarify to the dentist about the possible etiological factors responsible for such complication, to identify its clinical and radiographic signs and to describe the surgical technique adopted in these cases. Case Report: For this purpose, the authors present the clinical case of a patient with post-exodontia oroantral fistula of the right permanent maxillary first molar. The proposed treatment was the closure of the fistula under local anesthesia using the Bichat adipose body, with advantages of being a simple procedure, easy to perform, that does not require specific material, minimal complications, low morbidity and can be performed in the own dental practice and with high success rates proven by several studies. Discussion: The oroantral fistula is a common pathological occurrence in the dental clinic, characterized by communication of the maxillary sinus with the oral cavity when the maxillary sinus is pneumatic or during dental extractions of upper posterior elements whose roots are closely related to the maxillary sinus. Conclusion: Communications should be treated immediately, if there are signs of inflammation it should be treated first, so that surgical correction can be performed later.